Analysis of Milkshake Beverage Sales using Apriori Algorithm - Sujito, Sujito; Idris, Muhammad; Kadir, Shaifany Fatriana; Nurdiyansyah, Firman (Lumina Infinity Academy Foundation, 2025)
This research discusses the application of Data Mining with the Apriori algorithm on milkshake drink sales to support Business Intelligence. The research process includes collecting sales transaction data, forming frequent itemsets, and analyzing association rules using metrics such as support and confidence. The results show that product combinations, such as Chocolate and Strawberry, have high purchase rates with support reaching 75% and confidence up to 75%. These findings provide important insights for business owners in designing more effective marketing strategies, including promotions and stock management optimization. By utilizing the Apriori algorithm, this research successfully identified significant purchase patterns that can drive growth and improve customer satisfaction in the food and beverage industry.